2012
DOI: 10.1016/j.ajic.2011.09.020
|View full text |Cite
|
Sign up to set email alerts
|

Adoption of policies to prevent catheter-associated urinary tract infections in United States intensive care units

Abstract: Background Little is known about whether recommended strategies to prevent catheter-associated urinary tract infection (CAUTI) are being implemented in intensive care units (ICU) in the United States. Objectives Our objectives were to describe the presence of and adherence to CAUTI prevention policies in ICUs, to identify variations in policies based on organizational characteristics, and to determine whether a relationship exists between prevention policies and CAUTI incidence rates. Methods Four hundred … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
1
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 25 publications
(38 reference statements)
3
17
1
3
Order By: Relevance
“…Prior work has suggested that larger teaching hospitals, which typically care for more medically complex patients, have a higher incidence of CAUTI and may be less likely to adopt CAUTI prevention policies. 32 Compared with recent data submitted by NHSN participating hospitals, we found greater differences in catheter utilization and CAUTI within non-ICU settings. Although the reporting of CAUTI in adult and pediatric ICUs to the NHSN has been mandated by the CMS since January 1, 2012, 33 reporting in non-ICU locations is not yet required.…”
Section: Discussioncontrasting
confidence: 40%
“…Prior work has suggested that larger teaching hospitals, which typically care for more medically complex patients, have a higher incidence of CAUTI and may be less likely to adopt CAUTI prevention policies. 32 Compared with recent data submitted by NHSN participating hospitals, we found greater differences in catheter utilization and CAUTI within non-ICU settings. Although the reporting of CAUTI in adult and pediatric ICUs to the NHSN has been mandated by the CMS since January 1, 2012, 33 reporting in non-ICU locations is not yet required.…”
Section: Discussioncontrasting
confidence: 40%
“…12 A recent study by Conway and colleagues also revealed that adoption of policies to prevent CAUTI in intensive care units (ICUs) is lacking, with only 42% of ICUs reporting having written policies in place for at least 1 of 4 prevention practices: use of portable bladder ultrasound scanners, condom catheters for men, urinary catheter reminders or stop-orders, or nurse-initiated urinary catheter discontinuation. 13 …”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that hospitals with more than 500 beds, as well as teaching hospitals and medical–surgical intensive care units (ICUs), report more cases of CAUTI compared with smaller hospitals . Patients who are older, female, bedridden or hospitalized for more than 7 days, and patients with malignant tumours, diabetes, renal failure and long‐term catheterization are at the highest risk of CAUTI …”
Section: Introductionmentioning
confidence: 99%